The multifaceted role of m5C RNA methylation in digestive system tumorigenesis - Hu, Xinjun; Liu, Yafeng; Zhang, Shujun; Liu, Kaijie; Gu, Xinyu (Frontiers in Cell and Developmental Biology, 2025)
5-Methylcytosine (m5C) is a widespread RNA methylation modification, wherein a methyl group is enzymatically transferred to specific RNA sites by methyltransferases, such as the NSUN family and DNMT2. The m5C modification not only impacts RNA structure and stability but also governs post-transcriptional regulation by influencing RNA transport, translation, and protein interactions. Recently, the functional importance of m5C in complex diseases, including cancer, has gained substantial attention. Increasing evidence highlights the critical roles of m5C in digestive system malignancies, where it contributes to tumor progression by modulating oncogene expression and regulating processes such as tumor cell proliferation, migration, invasion, and resistance to chemotherapy. Furthermore, m5C’s involvement in non-coding RNAs reveals additional dimensions in elucidating their roles in cancer. This review summarizes recent advances in m5C RNA methylation research within digestive system tumors, focusing on its functional mechanisms, clinical significance, and potential applications. Specifically, it aims to explore m5C’s role in tumor diagnosis, prognosis, and treatment, while proposing future directions to address current challenges and broaden its clinical utility.